Tryptophan and/or canthaxanthin in quail diets: effects on performance, carcass traits, hematology, blood chemistry and hepatic antioxidant capacity - Khaled H. El-Kholy; Mohamed E. Sokariaa; Mohammed F. El Basuini; Sara F. Fouda; Tarek A. Ebeid; Ibrahim T. El-Ratel; Mahmoud M. Azzam; Alessandro Di Cerbo; Ahmed A. Elolimy; Mahmoud Madkour; Mahmoud Alagawany (Poultry Science)
To enhance the health and performance of poultry, novel approaches have to be created. Using appropriate nutritional interventions to enhance body physiology and thus enhance productivity is one of these approaches. The purpose of the present investigation intended to examine how growing quail physiology and growth is affected by supplementing diets with tryptophan (Trp) and/or canthaxanthin (CX). The sum of 200 unsexed, 1-week-age Japanese quails (Coturnix coturnix japonica), with a nearly similar body weight (BW) of 33.50 ± 1.20 g, were assigned, in random, to four experimental groups. Each group consisted of five replicates, with 10 birds per replicate. Chicks in group 1 (T1) served as the control and were fed a basal diet without any supplementation from week 1 to week 5. The second (T2) and third (T3) groups received feed supplemented with 0.01 % Trp and 0.005 % CX, respectively. The fourth group (T4) was given a diet containing a combination of 0.01 % Trp and 0.005 % CX. Results indicated that supplementation with Trp, CX, or their combination significantly (P < 0.05) enhanced live BW and body weight gain (BWG) at 5 weeks. No noticeable variations in carcass characteristics were found across all treatments over the whole trial duration. Blood levels of high-density lipoprotein were considerably greater in the Trp and/or CX-fed group than in the control group. Adding Trp and/orCX to quail diets significantly (P < 0.05) decreased the activity of liver enzymes (alanine transaminase, ALT; aspartate transaminase, AST; alkaline phosphatase, ALP), along with reduced low-density lipoprotein (LDL) levels. Birds received diets with Trp and/or CX had higher values of antioxidant indices in serum and liver (P < 0.05), accompanied by low values of malondialdehyde compared to control group. We concluded that adding quail diet with Trp and/orCX had positive consequences on the growth performance and some physiological indices.